Quail (Coturnix coturnix japonica) Fermented Manure as a Fertilizer to Support Azolla microphylla Growth Rate - Jennifer Adelia Latif; Ramadhani Eka Putra; Rika Alfianny (Caraka Tani: Journal of Sustainable Agriculture, 2023)
Azolla (Azolla microphylla) is a potential livestock feed due to its fast-growing and relevant nutrient content. Quail farming generates manure as a by-product that can be used as fertilizer to support plant growth. This study aims to determine the dose effect of fermented quail manure on the growth rate of Azolla, as well as the nutritional content of the resulting Azolla biomass. The data were obtained through observation in 20 Azolla culture ponds according to the design method throughout the research for the Azolla growth rate parameters and laboratory tests to analyze manure and Azolla proximate content at the end of the study. The results showed that treatment of 50, 100 and 150 g m-2 of quail manure gave similarly good effects on the Azolla growth parameters, indicating that the application of quail manure can significantly increase the production of Azolla biomass in culture ponds. The resulting Azolla biomass from all treatments gave a value of 93% to 95% moisture content, 18% to 19% ash content, 36% to 42% protein, 20% to 37% fiber, 2.8% to 4% fat and 5% to 6% carbohydrates. Looking at the big picture, therefore, 100 g m-2 manure treatment is considered the most optimal among the rest. Based on the result obtained, this study can provide an overview of the dose of quail manure that can be used to support the growth of Azolla.